Extended-spectrum beta-lactamase in Escherichia coli isolated from humans, animals, and environments in Bangladesh: A One Health perspective systematic review and meta-analysis - Md. Saiful Islam; A.M.M. Taufiquer Rahman; Jayedul Hassan; Md. Tanvir Rahman (One Health, 2023)
Extended-spectrum beta-lactamase (ESBL)-producing Escherichia coli has been linked to both life-threatening hospital- and community-acquired infections across the globe. Here, we conducted a systematic review and meta-analysis to evaluate the prevalence of ESBL in E. coli isolated from humans, animals, and environments in Bangladesh. Following the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines, the current systematic review and meta-analysis was taken into account for studies published between 2010 and 2021 in peer-reviewed journals. The meta-analysis was performed on “R” version 4.2.2. A total of 36 studies were included in this systematic review and meta-analysis; among them, 22 were human, seven were animal, four were environmental, and three were multidisciplinary studies. The meta-analysis revealed that the pooled prevalence of ESBL-producing E. coli in Bangladesh was 21% (95% CI: 15%–27%). On the sample basis, the pooled prevalence of ESBL-producing E. coli in humans, animals, and environments was 17% (95% CI: 11%–23%), 22% (95% CI: 9%–34%), and 39% (95% CI: 16%–62%), respectively. All the pooled prevalence of ESBL-producing E. coli showed substantial heterogeneity (I2 > 75%; p < 0.05) among the selected studies. This systematic review reported 13 different types of resistance genes encoding ESBL, such as blaTEM-1 (37.5%), blaCMY (34.6%), blaCTX-M-1 (20.7%), blaCTX-M-15 (16.1%), blaTEM (12.3%), blaCTX-M and blaOXA (9.6%), blaOXA-1 (5.8%), blaampC (3.9%), blaSHV (3.8%), blaCMY-2 (2.3%), blaCTX-M-14 (1.3%), and blaCTX-M-9 (0.3%). Moreover, 39 types of epidemiologically important clones (including ST10 and ST131) were detected in ESBL-producing E. coli isolated from humans, animals, and environments in Bangladesh. To the best of our knowledge, this is the first systematic review and meta-analysis of integrated studies on ESBL-producing E. coli using the One Health approach in Bangladesh. The high prevalence of ESBL-producing E. coli, their resistance genes, and epidemiologically important clones in humans, animals, and environments highlights the importance of implementing comprehensive antimicrobial resistance (AMR) surveillance under a One Health perspective to mitigate the AMR consequences in Bangladesh.